Formulasi dan Evaluasi Tablet Urea Lepas Lambat Berlapis Biopolimer Poliasam Laktat Sebagai Suplemen Ruminansia - Bilqis Nurganiyu; Akmal Djamaan; Rini Agustin; Rusmana Wijaya Setia Ningrat (Journal of Pharmaceutical and Health Research, 2023)
Urea is a source of non-protein nitrogen (NPN) which can be used to replace pure protein in ruminants. Urea is easily soluble and is degraded to ammonia by rumen bacteria, thus affecting the quality of ruminants. To increase the utilization of urea as a supplement is to try to slow its release into ammonia in the rumen so that it can be used efficiently by rumen microbes to form microbial protein. Slow release urea tablets as an alternative can control the rate of urea degradation and release of ammonia into the rumen and increase rumen efficiency. This study aims to determine the rate and pattern of release of urea tablets in the rumen so that their use is more practical and the dosage is correct. To maintain ammonia levels in the rumen, an alternative polymer-coated urea slow release tablet was designed. Based on this, it was carried out to manufacture slow release urea tablets with biopolymer polylactic acid (PLA) coating in the rumen fluid of ruminants. Furthermore, an in vitro evaluation was carried out by measuring pH into rumen fluid and measuring NH3 by UV-Vis spectro analysis at a wavelength of 630 nm. The results of the test for urea release in the rumen in formulas 1, 2 and 3 were 75.133%, 76.076% and 74.051% respectively, while the release of urea in uncoated urea tablets was 96.384%, these results indicate that tablets with lactic acid coated polyacid last longer. release compared to urea tablets without biopolymer coating.